Implementation barriers and enablers of midwifery group practice for vulnerable women: a qualitative study in a tertiary urban Australian health service - Patricia A Smith; Catherine Kilgour; Deann Rice; Leonie K Callaway; Elizabeth K Martin (BMC, 2022)
Abstract Background Maternity services have limited formalised guidance on planning new services such as midwifery group practice for vulnerable women, for example women with a history of substance abuse (alcohol, tobacco and other drugs), mental health challenges, complex social issues or other vulnerability. Continuity of care through midwifery group practice is mostly restricted to women with low-risk pregnancies and is not universally available to vulnerable women, despite evidence supporting benefits of this model of care for all women. The perception that midwifery group practice for vulnerable women is a high-risk model of care lacking in evidence may have in the past, thwarted implementation planning studies that seek to improve care for these women. We therefore aimed to identify the barriers and enablers that might impact the implementation of a midwifery group practice for vulnerable women. Methods A qualitative context analysis using the Consolidated Framework for Implementation Research was conducted at a single-site tertiary health facility in Queensland, Australia. An interdisciplinary group of stakeholders from a purposeful sample of 31 people participated in semi-structured interviews. Data were analysed using manual and then Leximancer computer assisted methods. Themes were compared and mapped to the Framework. Results Themes identified were the woman's experience, midwifery workforce capabilities, identifying "gold standard care", the interdisciplinary team and costs. Potential enablers of implementation included perceptions that the model facilitates a relationship of trust with vulnerable women, that clinical benefit outweighs cost and universal stakeholder acceptance. Potential barriers were: potential isolation of the interdisciplinary team, costs and the potential for vicarious trauma for midwives. Conclusion There was recognition that the proposed model of care is supported by research and a view that clinical benefits will outweigh costs, however supervision and support is required for midwives to manage and limit vicarious trauma. An interdisciplinary team structure is also an essential component of the service design. Attention to these key themes, barriers and enablers will assist with identification of strategies to aid successful implementation. Australian maternity services can use our results to compare how the perceptions of local stakeholders might be similar or different to the results presented in this paper.